House of correction [large type] : a novel - French, Nicci (Harper Large Print, an imprint of HarperCollinsPublishers, 2020)
Attempting to solve her own case from the confines of prison, a reclusive murder suspect from an English village uncovers evidence that calls her own sanity into question.